Severe acute ischemic colitis: What is the place of endoscopy in the management strategy? - Lorenzo, Diane; Barthet, Marc; Serrero, Mélanie; Beyer, Laura; Berdah, Stéphane; Birnbaum, David; Vitton, Véronique; Gonzalez, Jean Michel (Endoscopy International Open, 2021)
Background and study aims Ischemic colitis (IC) is potentially lethal. Clinical and biology information and results of computed tomography (CT) scan and/or colonoscopy are used to assess its severity. However, decision-making about therapy remains a challenge.Patients and methods This was a retrospective, single-center study between 2006 and 2015. Patients with severe IC who underwent endoscopic evaluation were included. The aims were to determine outcomes depending on endoscopic findings and assess the role of endoscopy in the management.Results A total of 71 patients were included (men = 48 (68%), mean age = 71 ± 13 years). There was hemodynamic instability in 29 patients (41 %) and severity signs on CT scan in 18 (38 %). Twenty-nine patients (41 %) underwent surgery and 24 (34 %) died. The endoscopic grades were: 15 grade 1 (21 %), 32 grade 2 (45 %), and 24 grade 3 (34%). Regarding patients with grade 3 IC, 55 % had hemodynamic instability, 58 % had severity signs on CT scan, 68 % underwent surgery, and 55 % died. The decision to perform surgery was based on hemodynamic status in 62 % of cases, CT scan data in 14 %, endoscopic findings in 10 %, and other in 14 %. Colectomy was more frequent in patients with grade 3 IC (P < 0.05). A mismatch between mucosal aspect (necrosis) and serous (normal) was observed in 13 patients (46 %). Risk factors for colectomy in univariate analysis were aortic aneurysm surgery, hemodynamic instability, no colic enhancement on CT scan, and endoscopic grade 3. Risk factors for mortality in multivariate analysis were hemodynamic instability, colectomy, and Charlson score > 5 (P < 0.05).Conclusions This study suggests a low impact of endoscopy on surgical decision making. Hemodynamic instability was the first indication for colectomy. A discrepancy between endoscopic mucosal (necrosis) and surgical serous (normal) aspects was frequently noted.